Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1021/jp064740r
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Tip-Enhanced Raman Spectroscopy with Silver Tips

Abstract: We present single molecule tip-enhanced resonance Raman spectra from brilliant cresyl blue (BCB) submonolayers adsorbed on a planar Au surface with Ag tips. A gap of 1 nm between a Ag tip and the Au substrate was employed to create a highly enhanced electric field and to generate Raman scattering from an area of ∼100 nm 2 . Three lines of evidence are presented to prove the single molecule sensitivity of our experiments: (1) Extremely diluted samples were used. Estimations show that at most a few molecules wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
332
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(340 citation statements)
references
References 36 publications
6
332
0
2
Order By: Relevance
“…Leveraging the increased Raman scattered light output of SERS with the highly localized field enhancement of apertureless SNOM, it is possible to create sub-diffraction-limited spectroscopic images with TERS that provide sufficient light output for detection. [145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160] …”
Section: Applicationmentioning
confidence: 99%
“…Leveraging the increased Raman scattered light output of SERS with the highly localized field enhancement of apertureless SNOM, it is possible to create sub-diffraction-limited spectroscopic images with TERS that provide sufficient light output for detection. [145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160] …”
Section: Applicationmentioning
confidence: 99%
“…They claimed that they can attain SM sensitivity because the Raman band from brilliant cresyl blue shows fluctuations in intensity and to a minor extent also in frequency [83,86], which is a possible indicator for SM behaviour as discussed in §2 (the characteristics of SM-SERS). Another popular dye used for SM-TERS study is malachite green isothiocyanate [58,87,88], which has a strong adsorption band centred around the excitation line at 632.8 nm and exhibits strong fluorescence as reported by Domke et al [89].…”
Section: Devices/systems For Single-molecule Surfaceenhanced Raman Spmentioning
confidence: 99%
“…39 Also, in a study of the distribution of localized site Raman enhancements on nanostructured Ag substrates it was found that over 50% of the Raman signal originated from less than 1% of the molecules. 9 Clearly, it takes only a very small percentage of hot-spot area to make a substantive difference to the average SERS EF.…”
mentioning
confidence: 99%